1977
DOI: 10.1051/jphys:0197700380120149300
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering and local order in GexSe 1 -x glasses for 1/3 ≤ x ≤ 1/2

Abstract: Having previously studied the local order of GexSe1-x glasses between pure selenium and x = 1/3, we have now prepared samples for 1/3 ≤ x ≤ 1/2. Glassy materials have been obtained up to x = 0.44 and, at higher x values, the samples are made of GeSe crystallites embedded in a glassy matrix of GexSe1-x, with x = 0.41 ± 0.01, the percentage of glass going to zero when x goes to 1/2. Raman scattering measurements have been performed on a set of such samples, at room temperature. The results lead to the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

1977
1977
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 12 publications
1
10
0
2
Order By: Relevance
“…These two features remain unchanged before and after thermal annealing, indicating the host material is stable, and implantation and annealing have not resulted in detectable changes in the chemical bonding. The growth of features at 150cm −1 and 175cm −1 after 10 hours of annealing has occasionally been seen in un-doped films of Ge 11.5 As 24 Se 64.5 and is thought to be a result of nanoscale phase separation and the appearance of a GeSe or As 4 Se 4 phase [24,25]. It is therefore not considered to be due to the erbium doping or ion implant processes.…”
Section: Resultsmentioning
confidence: 99%
“…These two features remain unchanged before and after thermal annealing, indicating the host material is stable, and implantation and annealing have not resulted in detectable changes in the chemical bonding. The growth of features at 150cm −1 and 175cm −1 after 10 hours of annealing has occasionally been seen in un-doped films of Ge 11.5 As 24 Se 64.5 and is thought to be a result of nanoscale phase separation and the appearance of a GeSe or As 4 Se 4 phase [24,25]. It is therefore not considered to be due to the erbium doping or ion implant processes.…”
Section: Resultsmentioning
confidence: 99%
“…6 indicates that the first peak position in the amorphous gr agrees not with the nearest bond length in crystalline GeS, but with that in crystalline GeS 2 , which is made up of connecting GeS 4a2 tetrahedra. Further, Tronc et al [17] have reported that the Raman spectrum of crystalline GeSe has two strong peaks at 150 and 187 cm À1 , respectively. In Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Solin and Papatheodorou [26] have observed also many sharp lines in the Raman spectra of as-' ) These results on the vibrational properties of the Ge-rich Gel -& glasses are also consistent with the vibrational properties of Ge-rich Gel-,Se, glasses studied by Tronc e t al. [25].…”
Section: > 14 Atyo Gtmentioning
confidence: 95%